The role of gaze in meaning negotiation episodes in video synchronous computer-mediated interactions - Li Chenxi (Journal of China Computer-Assisted Language Learning)
The outbreak of COVID-19 led to the replacement of many traditional classroom teaching and learning activities with online interactions through synchronous audio or video conferencing tools. Technically, the key difference between audio and video conferencing is the latter’s use of a webcam. Therefore, this study aims to investigate the webcam’s role in video synchronous computer-mediated communication (SCMC). Negotiation for meaning episodes, in which interlocutors try to resolve non-understanding through verbal interaction, were selected for analysis because they are widely believed to be helpful for second language acquisition. Specifically, this paper focuses on where interlocutors look during negotiated interactions in video SCMC and whether a statistical relationship exists between looking at a peer’s video image and successful meaning negotiation. Four dyads of English learners completed information gap tasks with potentially unknown words through learner–learner video SCMS interactions. Students’ multimodal performance was screen recorded for a gaze analysis and one-on-one interviews were conducted to confirm the students’ gaze directions. The results reveal a statistically significant positive relationship between the duration of one’s gaze at the peer’s video image and the number of successful meaning negotiation episodes in a dyad.